Tunable nonpolarizing one-dimensional crossed resonant gratings incorporating electrically driving liquid crystal. (11th February 2019) - Ren, Zhibin; Sun, Yahui; Lin, Zihao; Wang, Chunyu
Abstract: A tunable nonpolarizing filter composed of one-dimensional crossed resonant gratings and an electrically driving liquid crystal (LC) cell is designed, fabricated and demonstrated. The filter is designed by using different grating periods to obtain nonpolarizing spectra for oblique incidence. The filter sample is fabricated through thin-film deposition, ultraviolet lithographic patterning, deep reactive ion etching and LC injection. Finally, the resonance spectra of the fabricated sample are measured by a spectrometer and the measured results are consistent with the theory. The experimental results show that the nonpolarizing resonance spectra can be tuned by electrically driving the LC cell of the proposed device.